Hadis Sahih dan Mutawatir: Satu Perbandingan Antara Sunni dan Syi'ah Imamiyyah - Abdul Sukor, Abdul Hayei (Jurnal Usuluddin, 1995)
The need of classification in the condition of the Hadis valuation between Sunni and Syi'ah Imamiyyah. The impact from the classification effect the 'hukm' between the two mazhab. This article discusses directly regarding the condition of the two medium of mazhab in using hadith. This article discusses the conditions where fix by Syi'ah Imamiyyah.